Electrohydrodynamic (EHD) jet printing with a circulating dual-channel nozzle. (31st January 2019) - Li, Zhen; Al-Milaji, Karam Nashwan; Zhao, Hong; Chen, Da-Ren
Abstract: Electrohydrodynamic (EHD) printing is a promising technique for additive manufacturing of high-resolution features with low cost and high efficiency. One of the major issues in EHD printing is nozzle clogging, which often occurs in the printing of colloidal inks with high concentrations. We proposed a new EHD printing nozzle configuration with dual channels to enable ink flow circulation to resolve the above issue. In this study, we focused on the meniscus dynamics and jetting characteristics of this new EHD printing process. Various jetting modes, i.e. continuous jet, pulsating jet, and pulsating droplet, as a function of the electric field intensity and nozzle configuration, were discussed. Dot patterns on a flexible substrate have been demonstrated via the new EHD printing process when operated at the pulsating droplet mode.